Blood Vessel Epicardial Substance (BVES) in junctional signaling and cancer. Issue 4 (2nd October 2018) - Parang, Bobak; Thompson, Joshua J.; Williams, Christopher S.
ABSTRACT: Blood vessel epicardial substance (BVES) is a tight-junction associated protein that was originally discovered from a cDNA screen of the developing heart. Research over the last decade has shown that not only is BVES is expressed in cardiac and skeletal tissue, but BVES is also is expressed throughout the gastrointestinal epithelium. Mice lacking BVES sustain worse intestinal injury and inflammation. Furthermore, BVES is suppressed in gastrointestinal cancers, and mouse modeling has shown that loss of BVES promotes tumor formation. Recent work from multiple laboratories has revealed that BVES can regulate several molecular pathways, including cAMP, WNT, and promoting the degradation of the oncogene, c-Myc. This review will summarize our current understanding of how BVES regulates the intestinal epithelium and discuss how BVES functions at the molecular level to preserve epithelial phenotypes and suppress tumorigenesis.